Intravitreal Nesvacumab (Anti-Angiopoietin-2) Plus Aflibercept in Neovascular AMD: Phase 2 ONYX Randomized Trial. (January 2023) - Heier, Jeffrey S.; Ho, Allen C.; Boyer, David S.; Csaky, Karl; Vitti, Robert; Perlee, Lorah; Chu, Karen W.; Asmus, Friedrich; Leal, Sergio; Zeitz, Oliver; Cheng, Yenchieh; Schmelter, Thomas; et al.
Purpose: To compare intravitreal nesvacumab (anti-angiopoietin-2) + aflibercept vs intravitreal aflibercept injection (IAI) in neovascular age-related macular degeneration (nAMD). Methods: Eyes were randomized (1:2:3) to nesvacumab 3 mg + aflibercept 2 mg (LD combo), nesvacumab 6 mg + aflibercept 2 mg (HD combo), or IAI 2 mg at baseline, week 4, and week 8. The LD combo was continued every 8 weeks (q8w). At week 12, the HD combo was re-randomized to q8w or every 12 weeks (q12w) and IAI was re-randomized to q8w, q12w, or HD combo q8w through week 32. Results: The study comprised 365 eyes. At week 12, the mean best-corrected visual acuity (BCVA) gains from baseline were similar in the LD combo group, HD combo group, and IAI group (5.2 letters, 5.6 letters, and 5.4 letters, respectively); the mean central subfield thickness (CST) reductions were similar (182.2 µm, 200.0 µm, and 178.6 µm, respectively). The mean changes in BCVA and CST through week 36 were similar across groups. At week 12, complete retinal fluid resolution was observed in 49.1% (LD combo), 50.8% (HD combo), and 43.6% (IAI) of eyes; the proportions with a CST of 300 μm or less were similar across groups. Numerical trends at week 32 toward complete retinal fluid resolution with combination treatment were not maintained at week 36. Serious ocular adverse events were infrequent and comparable across groups. Conclusions: In nAMD, nesvacumab + aflibercept showed no additional BCVA or CST benefit over IAI monotherapy.